Using the Pandemic for Their Own Gain: The Experiences of COVID in Serbia - Uzelac, Mirjana (Anthropologica, 2023)
The paper analyzes the experiences of older adults (65 years of age and older) with the COVID-19 pandemic in Serbia. At the beginning of the pandemic, the Serbian government declared a national state of emergency, which included a strict curfew in which older adults were forbidden to leave their homes under any circumstances. After 52 days, the state of emergency was lifted, which was soon followed by a rapid loosening of coronavirus measures. During this time, Serbia held parliamentary elections that were rife with irregularities. The government was accused of using the pandemic for political gains, including fabricating the numbers of COVID-19 deaths. The interlocutors in the study mapped their experiences with these measures and recounted how their lives had changed since the early days of the pandemic and into 2022. All interlocutors chose to frame their experiences through their criticism of the government and how it mishandled the pandemic. Rather than making excuses for a weaker government, the criticism is based on interlocutors’ expectations of a capable statecraft that can take care of its people, and the inability of the existing government to fulfill these expectations. Through the experiences of the pandemic, the study examines the tensions between the government and people in Serbia’s post-socialist context, and how these tensions are heightened during the time of crisis.